Planejamento e confecção de um material didático digital para realização de atividades de ensino por professores em ambientes hospitalares. - SILVA, Sarah Raquel Froes da (2021)
According to the technological development process running through social interactions, digital technologies are integrated in the forms of entertainment, day to day communication as well as the worldwide sharing of information via multiple platforms. As a faithful comrade, digital mobile devices such as smartphones and tablets expand the possibilities for users to be in several places at the same time and update themselves on what happens beyond the walls of their home along with assisting students in and outside of the classroom enviroment. For that reason, there are school spaces in which mobile digital technologies may come to act upon the very same purpose, with their users and enhance educational functions, one of which is Hospital Classes who is intended to provide schooling for students away from attending regular classes due to medical treatments. Meaning to strengthen the educational, affective and interactivity processes between students and teachers in the Hospital Class of “ABC” Nefro, this thesis aimed to design a digital didactic material in the likeness of an E-book, contemplating pedagogical sequences for the construction of digital resources learning, including educational digital apps. As means of crafting such material, a researcher carried out a survey on the pedagogical practices at the Hospital Class “ABC” Nefro, through structured appointments with the teachers who served this Hospital Class and their responses were analyzed in complience with the content analysis of Bardin (2011). The research had the development methodology as a methodological basis and the nature of its approach was qualitative in order to unify the Hospital Class teachers’ knowledge, developed thourgh years of practice, as well as researches on digital applications and cross-cutting themes on mobile devices, all inserted in the material presented to students of the Unidade Presidente Dutra University Hospital.